Medical residents' mental distress in the COVID-19 pandemic: An urgent need for mental health care. - Amanda Steil; Ana Bresser Pereira Tokeshi; Luca Silveira Bernardo; Geraldo Pio da Silva Neto; Ronald Ferreira Davi; Amanda Ferreira Santa Bárbara; Vitor S Mendonca; Thiago M Fidalgo; Aécio Flávio Teixeira Gois (PLoS ONE, 2022)
Purpose Medical residents' mental health is currently an issue of concern for medical educators worldwide. The COVID-19 pandemic has raised the greatest concerns given the psychological effects of this scenario on medical residents on the frontlines of the pandemic. To assess the psychological impact of the COVID-19 pandemic on physicians in residency training, the collective symptoms of burnout, depression and anxiety are used to identify the residents' beliefs and clinical practices related to COVID-19 patients and their behaviors concerning disease prevention. Method This observational study involved 3071 medical residents from all regions of Brazil. An online questionnaire assessed the presence of burnout using the Oldenburg Burnout Inventory, depressive symptoms using the Patient Health Questionaire-9, anxiety symptoms using the Generalized Anxiety Disorder-7, and COVID-19 Impact Questions to assess the residents' beliefs and clinical practices related to COVID-19 patients. Exploratory analyses, logistic regression and multinomial regression analysis were performed in this investigation. Results Moderate and severe depressive symptoms were the most common (67.7%) followed by anxiety symptoms (52.8%) and burnout (48.6%). The difference between residents with or without contact with COVID-19 patients was significant increased when analyzing different aspects of clinical practice, behavior, substance use and mental health. Conclusions These results suggest an increase in depression and anxiety symptoms among medical residents dealing with COVID-19, upstaging previous concerns about medical residents' mental health. The prevalence of burnout is similar to that of a nonpandemic scenario. Considering the severity of the pandemic scenario and the overburden of healthcare services, medical residents' mental health deserves special care.